Impact of International Financial Reporting Standards on Private Educational Units - Alex Vinicio Iñiguez-López; Cecilia Ivonne Narváez-Zurita; Juan Carlos Erazo-Álvarez (Revista Arbitrada Interdisciplinaria Koinonía, 2020)
This research takes as reference the implementation of international regulations in the education sector, with the aim of measuring the benefits that the South American Educational Unit has had when applying International Financial Reporting Standards (IFRS) in the preparation of its financial statements. The study had a mixed-methods approach; the qualitative part allowed identifying the characteristics and processes of the IFRS regulations applied to the analysis unit, while the quantitative part allowed analyzing the accounting information for the 2014-2018 periods using financial tools. As a result of this general analysis, it was evident that the adoption of IFRS brought difficulties from its inception, however, when performing the budgetary analysis of the most important items in the monetary statements, it was determined that for the year 2018, the entity Educational presented a faithful image of its operations and financial situation.